ORGANIZATIONAL AND INDIVIDUAL CAREER MANAGEMENT ON EMPLOYEE PERFORMANCE THROUGH AFFECTIVE COMMITMENT (A CASE STUDY AT INDONESIAN POST OFFICE OF BOYOLALI BRANCH) - Muhammad Nujulul Huda; Fitri Wulandari (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
This study aims to investigate the effect of organizational and individual career management on employee performance through affective commitment (a case study at Indonesian Post Office of Boyolali Branch). The research subject was employee performance. Including the type of quantitative research. The research sample was 62 employees of Indonesian Post Office of Boyolali Branch using a convenience sampling technique. Data were analyzed using the SmartPLS analysis technique. The results indicate that organizational career management has a significant positive effect on affective commitment, with a t-statistic value of 2.041. Then individual career management with a value of 0.886 has no significant effect on affective commitment. Organizational career management has no significant effect on employee performance with a value of 0.425. Individual career management also has an insignificant effect on employee performance with a value of 0.685. Affective commitment involvement has a significant effect on employee performance with a value of 2.168. The role of mediating affective commitment to the influence of organizational career management on employee performance is not mediating. Likewise in individual career management of employee performance through the value of affective commitment is not mediating